Pengaruh Disiplin Kerja, Lingkungan Kerja, Dan Kepemimpinan Terhadap Kinerja Karyawan UD. Timbul Jaya, Kec. Wates, Kab. Kediri - Sultan Bayu Ananta; Moch. Saleh Udin; Taufik Akbar (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
This research aims to determine the significance of the influence of work discipline, work environment, and leadership on employee performance at UD. Timbul Jaya, Wates Subdistrict, Kediri Regency. The sampling technique used in this research is saturation sampling with a total sample of 34 respondents. The analysis technique used includes Validity Test, Reliability Test, Classical Assumption Test (Normality Test, Heteroscedasticity Test, Linearity Test, and Multicollinearity Test), Multiple Linear Regression Analysis, t-Test, F-Test, and Coefficient of Determination (R2). The results of the research based on partial testing indicate that Work Discipline does not significantly affect the Employee Performance of UD. Timbul Jaya, Wates Subdistrict, Kediri Regency, the Work Environment significantly affects the Employee Performance of UD. Timbul Jaya, Wates Subdistrict, Kediri Regency, and Leadership does not significantly affect the Employee Performance of UD. Timbul Jaya, Wates Subdistrict, Kediri Regency. Simultaneous testing shows that Work Discipline, Work Environment, and Leadership have a significant impact on Employee Performance at UD. Timbul Jaya, Wates Subdistrict, Kediri Regency.